Halamphora ectoriisp.nov. - a new diatom species from saline spring Solenica in North Macedonia - Zlatko Levkov & Dusica Zaova (Nova Hedwigia, 2023)
Abstract: Saline springs are aquatic habitats inhabited by specific diatom flora. Recently several new species and genera have been described from such habitats. Spring Solenica is the only saline spring in Macedonia and it is not an exception. Observations of diatom assemblages in the spring reveal presence of several interesting species. One of them having unique morphological features is described here as Halamphora ectorii sp. nov. The new species has been observed by light and scanning electron microscope. It is characterized by semi-lanceolate valves with hyaline appearance, since the striae are densely spaced and composed of areolae with small, round external openings. Central area from both valve sides is broad and continues on valve mantle on dorsal side Halamphora ectorii is compared with several similar species from saline inland and costal habitats and main differential features are provided. This study highlights the importance of rare habitats to the diversity of the broader region
Keywords: diversity, halophile species, inland saline habitats, taxonomy